THE IMPLEMENTATION OF EGRA TECHNIQUE TO IMPROVE THE STUDENTS’ GRAMMAR MASTERY (A Classroom Action Research at the Second Semester of English Department of Madiun State Polytechnic in the Academic Year of 2017/2018) - Eda Maaliah; Muhyiddin Aziz (Humaniora Scientia, 2018)
This research aims to prove that EGRA technique (Experience, Generalization, Reinforcement,Application) can improve the students’ grammar mastery. It was conducted in State PolytechnicMadiun from April to September 2018. The subjects of the research were the second semesterstudents of English Department consisting of 27 students. This action research covered twocycles. Each consisted of planning, acting, observing, and reflecting. In this research theresearcher employed qualitative and quantitative data analysis. Based on the research findingsfrom teaching-learning process in the two cycles, the researcher can draw some finalconclusions. The students’ response was very good after implementing EGRA technique. Thestudents were active in giving answer of each question.. It was also shown from the improvementof the mean scores in every cycle as follows : mean score in pre-test was 63, post test in the firstcycle was 70, and  post-test in the second cycle was 80. There was improvement in every cycle.Additionally, there were 24 of 27 students who got point up 75 in the second cycle, it means itwas 89 %. Based on the finding, the alternative hypothesis stating that EGRA technique canimprove the students’ grammar mastery. Keywords: Implementation, EGRA Technique, and Grammar Mastery